Evaluation of the Family Hope Program in an Effort to Improve the Quality of Life for Poor Families - Oktavia Anggraini; Henny Aprianty; Bobby Mandala Putra; Heru Purnawan; Rahiman Dani (Journal of Social Science and Humanities, 2022)
This study aims to determine the effectiveness of the Family Hope Program on the aspects of the goals and impacts of Lubuk Sahung Village, Sukaraja District, Seluma Regency. The subject of this research is the Beneficiary Family in Lubuk Sahung Village which consists of 9 informants. Data collection methods used are interviews, observation, and documentation with data analysis techniques. The results showed that the Family Hope Program in Lubuk Sahung Village, Sukaraja District, Seluma Regency had been effective in the fields of education, health, and the community's economy. The results of the research on education indicators have been effective, the answers given by the informants did not find the ineffectiveness of the Family Hope Program in Lubuk Sahung Village. While the health sector output indicators in the category can be said to be quite effective from some information that received assistance in the health sector of the Family Hope Program that the health indicators have been implemented and utilized properly. Then the impact indicator on is good with changes in the economy of the beneficiary familiesof the Family Hope Program. In general, the Family Hope Program seen from the dimensions of its effectiveness, Lubuk Sahung Village has been running effectively.